Kyrgyz Republic : Poverty in the 1990s in the Kyrgyz Republic - World Bank (Washington, DC, 2013)
The study focuses on the high levels of poverty in the Kyrgyz Republic, where the trend has been one of increasing poverty in the last decade. The first chapter reviews the economic situation, based on data sources, particularly the household level data, collected by the National Statistical Committee, which measure not only the levels, and depth of poverty, but identifies the determinants of poverty, and other social outcomes and indicators as well. Economic growth dropped in the early 1990s, rose in 1996-97, and then fell in the wake of the Russian financial crisis, with significant lower resources available to the government. Furthermore, government spending as a share of GDP maybe at unsustainable levels, and may need to be reduced; this creates the dilemma that, as poverty increases, the government has fewer resources to provide assistance, and services. Chapter II presents an overview of poverty, indicating extreme poverty affected twenty three percent of the population, with a significant shortfall in consumption. Chapters III and IV explore the livelihoods of the poor, and issues affecting them, focused on the lower levels in labor force participation by the poor, the hidden differences in unemployment among the welfare groups, and, limited employment opportunities. Dissatisfaction concerning utilities, education, and health is prevalent, where the poor pay a disproportionately high share of total income (consumption) for services. Conclusions, and recommendations are presented in Chapter V, emphasizing on public spending policies targeting poverty, through social assistance programs, all of which will require sectoral reform, and rationalization of services.